Jazz. Episode six, Swing, the velocity of celebration [videorecording (DVD)] - Burns, Ken, 1953-; David, Keith; Davis, Ossie; Marsalis, Wynton, 1961- (PBS Home Video ; Distributed by Paramount Home Entertainment, 2004)
In the late 1930s, as the Great Depression deepens, jazz thrives. The saxophone emerges as an iconic instrument of the music; this segment introduces two of its masters, Coleman Hawkins and Lester Young. Young migrates to Kansas City, where a vibrant music scene is prospering with musicians such as trumpeter Harry "Sweets" Edison and drummers Jo Jones and Chick Webb. Out of this ferment emerges pianist Count Basie, who forms a band that epitomizes the Kansas City sound. Billie Holiday cuts recordings while other women musicians, including pianist Mary Lou Williams and singer Ella Fitzgerald emerge on the jazz scene. Benny Goodman holds the first-ever jazz concert at Carnegie Hall while Duke Ellington tours Europe.